DATA STORAGE PROJECT ON THE LINE WEB-BASED - Linda Wahyu Widianti (Majalah SIKOMTEK, 2005)
Data storage is the most important things done because it is a way for archiving files. Data storage is also a documentation of all activities will be oriented on the use and processing. In terms of data storage can not only be done on a computer or data storage across local network only, but in the current world development technology that is growing and the mobility of its users to follow the development of data storage can be done online. It is intended to facilitate the users to be able to store data anywhere, anytime. Will fully understand the performance of its users to be able to continue to work as closely as possible without knowing, time and place. So this is where the role of information technology is actually in use. With web media, it would not only be used for media publications, but also able to be used for storing data online.